PHYTO-CHEMICALS OF SOME PLANT LEAF POWDER AS ANTI-INSECT AGENTS AGAINST MAIZE WEEVILS Sitophilus zeamais (Coleoptera: Curculionidae) (FUDMA JOURNAL OF SCIENCES, 2023)
Leaf powder of Purple dead nettle (Lamium purpureum), Nut grass (Cyperus retrorsus), Wild sage (Lantana camara), Sunflower (Helianthus annuus), Key lime (Citrus aurantifolia) and Queen of the night (Cestrum nocturnum) were screened for secondary metabolite constituents and insecticidal activity against Maize weevil (Sitophilus zeamais). Phytochemicals screening of the powder revealed the presence of alkaloids, terpenoids, flavonoids, tannins, saponnins, phytosteroids, phenolic compounds, proteins and aminoacids, oil and fats as well as reducing sugars in the plants investigated. The plants powder indicates insecticidal activity in a dose dependent manner, higher doses has stronger effect, all the experimental plants caused significant mortalities (p
Keywords: Insecticidal activity, Powder, Phyto-chemical, Screening, Sitophilus zeamais